Effect of Medicinal Plants on Liver and Malaria Pathogenesis - Joel, Emmanuel Askeb-nde; Umaru, Isaac John; Iseko, Kingsley Iyoko; Istifanus, Dafup Katdel (Darul Yasin Al Sys, 2024)
This seminar reviewed the literatures on the effects of medicinal plants on liver and malaria pathogenesis. Malaria parasite has a complex life cycle that takes place both inside the mosquito and human beings. Generally, diagnosis of malaria is classified into clinical and parasitological diagnoses. Lack of clear understanding on the overall biology of Plasmodium (malaria), its life cycle and its mechanism of action has created a challenge in an effort to develop new drugs, and preventive methods against malaria such as using malaria vaccines and vector control. They have been a rise in the use of herbal supplements, natural products, and traditional medicines over the years. The use of herbal plants or their preparations in the management of various diseases including liver diseases has been practiced for several decades and its extension in current dispensation is recognized. It has been shown that the effect of medicinal plants is somehow related to belief, tradition and culture of the community. However, there are growing concerns related to the safety and toxicities of these medicines. These herbal medicines are associated with complications such as liver damage with a high incidence of mortalities and morbidities. Clinical manifestations range from asymptomatic cases with abnormal liver functions tests to sudden and severe liver failure necessitating liver transplantation. The liver is a very important organ with a lot of functions such as metabolism, detoxification, and storage of nutrients for the host to survive. Standard liver marker enzymes such as ALT, AST, ALP, albumin, globulin are essential when carrying out liver function tests. Medicinal plant components are essential for and can be beneficial or detrimental to the healthy or diseased liver. Medicinal Plants are an essential part of the human diet and comprise various compounds (photochemical) such as alkaloid (pyrrolizidine), kavalactone which are related to liver health. Selected medicinal plants can provide nutritional and medicinal support for liver diseases. At the present, the knowledge of the effects of medicinal plants on the liver is still incomplete. The most urgent task at the present time is to find the best dietary and medicinal plants for liver health in an endless list of candidates globally. This review updates the knowledge about the effects of medicinal plants consumption on the health of the liver, putting particular emphasis on the potential beneficial and harmful impact of medicinal plants on liver function.